THE EFFECTIVENESS OF THE MATHEMATICS LEARNING USING MODEL OF TEACHING RECIPROCAL OF THE STUDENTS’ LEARNING OUTCOMES OF SMP NEGERI 1 SAWANGAN MAGELANG REGENCY - Kirana Try Chandra Pertiwi; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The learning activity is still dominated by the teacher that makes students tending to be passive in participating in teaching and learning activity in the classroom. The students’ learning interest is low due to the students assume that mathematics is one of the difficult subjects, and it will affect the results of the students' mathematics learning. This research aims to find out the effectiveness of mathematics learning using the model of TeachingReciprocalof the students’ learning outcomes of 8class SMP Negeri 1 Sawangan Magelang regency Odd Semester Academic Year 2016/2017. The research population is all students of 8 class consisting of 6 classes. Sample is taken by using the sampling random technique of the classes and it is achieved by VIII B class as the experimental and VIII C as the control class. The data collecting technique is done by documentation and test method. The instrument used is the documentation paper of UTS value Odd Semester of 8 class students and the test question of learning outcomes. Data analysis techniques are hypothesis testing and precondition test of analysis including normality test and homogeneity test. The result of research shows (1)There are differences in the mathematics learning outcomes between students using the learning model of Teaching Reciprocal than students using the direct learning model. It is based on the first hypothesis test with a significance level of 5% and 61 freedom degree that it is achieved   = 2,38748 and  = 1,99996 then  rejected and  accepted. (2) The Learning Model of Teaching Reciprocal is more effective than the direct learning model on the results of students' mathematics learning. It is based on the second hypothesis test with a significance level of 5% and 61 freedom degree that it is achieved   = 2,38748 and  = 1,670385 then  rejected and  accepted.